“Implementación de una fresadora automatizada mediante control numérico computarizado para la elaboración de PCB para la Carrera de Electromecánica de la Universidad Técnica de Cotopaxi”. - Tapia Gaibor, Nelson David (2022)
In the Electromechanical major of Universidad Técnica de Cotopaxi, students require printed circuit boards (PCB) for their laboratory practices. Currently, they are made by using chemicals and acids, which have health risks, and environmental pollution, besides being unproductive and away from technology. In this project, in response to the problems of the students, seeking their welfare, and attachment to technology, this research is carried out on the implementation of an automated milling machine with numerical control for the production of PCBs in the institution. With the aim of providing facilities to students, minimizing risks, and making use of modern technologies, applying the method of machining with chip removal, with automated control of a milling machine, thus familiarizing the student with the latest industrial technology, in addition to having a highly productive process, low cost and safe for the user. In conclusion, we have that the machine speeds up the PCB manufacturing process, with great accuracy, this design applied knowledge of electronic automation and mechanical design.